2019
DOI: 10.22161/ijaers.6.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation for Data Volatility Analysis of Stock Prices in Islamic Finance for Malaysia Composite Index

Abstract: The objective of this study is to evaluate the volatility rate of sharia-company in Malaysia Stock Exchange using Monte Carlo Simulation (MCS). This study collected daily stock price form Thomson Reuters Datastream for calculating monthly return and volatility rate. In validating the findings of volatility rate, this study performed normality diagnostics test, and Monte Carlo Simulation (MCS). Result indicates the distribution of volatility rate is follows normal distribution. In addition, Monte Carlo Simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Thus, we concluded that the outliers detected in January 2008, September 2008 and January 2009 correspond to the recessionary period due to the world financial crisis. This finding demonstrates that IIS is a useful approach to identify outliers in financial data as compared to recent study using shariah compliant stock prices in Malaysia by [31]. This study differs from [31] research that was prone to methodological inadequacies due to inability of Box-Whisker plot to handle non-stationary data and to model the outliers detected.…”
Section: Empirical Applicationmentioning
confidence: 68%
See 1 more Smart Citation
“…Thus, we concluded that the outliers detected in January 2008, September 2008 and January 2009 correspond to the recessionary period due to the world financial crisis. This finding demonstrates that IIS is a useful approach to identify outliers in financial data as compared to recent study using shariah compliant stock prices in Malaysia by [31]. This study differs from [31] research that was prone to methodological inadequacies due to inability of Box-Whisker plot to handle non-stationary data and to model the outliers detected.…”
Section: Empirical Applicationmentioning
confidence: 68%
“…This finding demonstrates that IIS is a useful approach to identify outliers in financial data as compared to recent study using shariah compliant stock prices in Malaysia by [31]. This study differs from [31] research that was prone to methodological inadequacies due to inability of Box-Whisker plot to handle non-stationary data and to model the outliers detected. In addition, the box-whisker plot approach is not able to perform significance testing to the outliers captured compared to IIS in GETS modelling.…”
Section: Empirical Applicationmentioning
confidence: 68%
“…..…… 11The correlation coefficient for a sample can be derived as Equation (12). Consider the sample has n pair of x, y variables.…”
Section: B Modern Portfolio Theory For Developing Investment Portfoliomentioning
confidence: 99%
“…After Markowitz's work, researchers have shown great enthusiasm in portfolio management, trying different mathematical approaches to develop the theory of portfolio selection [10], [11]. Study that examine the volatility rate of sharia-compliant company listed on the Malaysian Stock Exchange using Monte Carlo Simulation method found that Monte Carlo Simulation proved the volatility rate is 4.85% and standard deviation is 2.23 [12]. The result shows the value of volatility rate is under statistical control with implementation of Monte Carlo Simulation approach [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation